Mechanical properties of translucent cement under the action of sodium sulfate and magnesium sulfate - et. al., Apirath Chattranusorn, (Turkish Journal of Computer and Mathematics Education (TURCOMAT), 2021)
This study is a study of Mechanical properties of translucent cement under the action of sodium sulfate and magnesium sulfate. The objectives of the study are: 1. to find the appropriate ratio to obtain a cement substitute for high compressive strength welding. The ratio of epoxy resin (translucent material) can be obtained at the lowest cost. 2. To study the influence of the electric oven energy curing condition on the compressive strength properties and physical properties corrosion resistance, both acid and base. 3. To study the feasibility of capping gypsum and resin that qualifies for construction work. From the property analysis and to estimate the duration of using capping gypsum and epoxy resin (Translucent material) cured by electric oven and room temperature conditions, it was found that the optimal ratio for obtaining the highest compressive strength cement replacement material was the by-weight ratio of epoxy resin of substance A and substance B is 100/60, baked at 80 degrees, soaked in water for 56 days to obtain a cement substitute for high compressive strength welding. The amount of water to be used mixed with high strength gypsum powder was 21%, duration 7 days, baked at 90 degrees and soaked in air. When considering the angle of use in construction instead of concrete, it was found that the most common ready-mixed concrete in the design of compressive strength ranging from 180-400 ksc and the most commonly used is 240 ksc cylinder. Therefore, when considered and found that Translucent cement under the action of sodium sulfate and magnesium sulfate. The compressive strength is between 200-800 ksc. General concrete work is mainly tested for the compressive strength. This is used to control the quality of work and can also be used as an indicator of other aspects as well. This is because the resistance to other forces is directly proportional to the compressive strength.